Development of a Capacitance-Based Biosensor for the Determination of Histamine Concentration - Wasoh @ Mohamad Isa, Helmi (2009)
Histamine level has been suggested as a rapid fish spoilage indicator. Besides that, a biosensor device with low cost, simple and portable is an advantage for fish freshness monitoring. Therefore, a histamine biosensor device was developed using the enzyme diamine oxidase (DAO) and a capacitance (C) concept. A capacitor with two plates system gives linear relationship between frequency (f) and histamine concentration. It has been proven that the relationship between f, dielectric constant (k) and histamine could be used to develop a histamine biosensor. The behavior of histamine reaction can be monitored in the presence of free enzyme in solution. Based on this relationship, immobilized enzyme electrode was developed by immobilizing 1.0 mg DAO/L in the ratio of DAO:polymer= 1:1. Good sensor response could be observed when the shape of the electrode was in a row and the electrode material was made from copper, with a distance between electrode, d=2.5 mm. By using this device, a linear range of histamine from 20 to 100 ppm was obtained (R2=0.9897) with good correlation between biosensor method and HPLC (R2 = 0.9998). For the determination of histamine in prawn tissues, the recovery obtained was 98.13% after spiking with 150 ppm histamine and 98.79% after spiking with 200 ppm histamine (average RSD, 1.16-5.67%). To complete the device, electronic reader was developed comprises PIC (peripheral integrated circuit) microcontroller, LCD (light crystal display), capacitor-resistor circuit and computer-programming in C code (installed in PIC). By using astable operation of capacitor-resistor circuit, a difference sensor response was generated from difference histamine concentration. During histamine reaction, the physicochemical changes was converted into electrical signal and translated in histamine concentration as part per million (ppm). PIC is very useful in modifying the writing process of computerprogramming due to its capability and easily reprogrammed. For the basic test (without enzyme), the device (with electronic reader) gave different (f) values for histamine (50-300 ppm, RSD≤2.01%). After the reader was developed successfully, enzyme electrode was designed with the dimension of copper material at d=2.0 mm and area, A=2.5x10 mm. By immobilizing enzyme onto this electrode, the device showed linear response to histamine concentrations (25 to 100 ppm, R2=0.998, RSD≤2.74%). The biosensor response was still 80% of the initial value after 10 days of storage (4oC). The histamine biosensor exhibited reproducibility characteristic with RSD value equals to 8.88% (n=4). This device can be used up to 30 times without a major change in sensor response (11.76±3.41 Hz/s). Experiment with prawn tissues shows that the performance of histamine biosensor device is comparable to HPLC with R2=0.9895. The histamine biosensor is a promising device for on site screening of fish freshness